University-industry collaboration and malaysian public universities funding model - Imaduddin, Abidin; Anita, Abdul Rani; Zarina, Mohd Ali; Jamal Rizal, Razali (IFRD, 2017)
The volatility of the global economy as a result of the falling oil prices worldwide has affected the domestic economy of Malaysia as a whole. This scenario has consequently changed the landscape of the Malaysian education industry, particularly in the management of the 20 public universities all over Malaysia. The shrinking operating budget allocated by the Ministry of Higher Education (MoHE) from total funding to only 70 percent has changed the public universities funding model in seeking financial resources to cope with the shortcomings.Thus, this paper aims to discuss the impact of educational budget cuts on the Malaysian public universities and propose practical solutions to overcome this impact on operating expensesof these universities from the viewpoint of the stakeholder theory. Key to our recommendation is the establishment of university-linked companies (ULCs) that are adapted based on the existing model of the Malaysian Government-linked Companies (GLCs) through University-Industry Collaboration (UIC).